Meningkatkan Hasil Belajar Matematika Materi Luas Bangun Ruang Melalui Penggunaan Media Bangun Ruang pada Siswa Kelas VI SD Negeri Kaloy - Evi Purnama Bayu Ningsih (Jurnal Bima : Pusat Publikasi Ilmu Pendidikan Bahasa dan Sastra, 2023)
This classroom action research aims to improve student learning outcomes by using media in mathematics learning for class VI students at SD Negeri Kaloy. Research includes Classroom Action Research. The subjects of this research were class VI students at SD Negeri Kaloy in the 2022/2023 academic year, totaling 27 students consisting of 14 male students and 13 female students, a class teacher, and a colleague. The techniques used to collect data in this research are observation and test techniques. The data obtained is in the form of test results and observation results as supporting data. The research data were analyzed using qualitative descriptions to describe the results of observations and quantitative descriptives to describe the percentage of test results in each cycle. The results of the research show that the use of spatial props can improve the quality of mathematics learning for class VI students at SD Negeri Kaloy. The results of the initial ability test (Cycle I) showed that of the 27 class VI students, only 11 students could be declared complete in learning by getting a score ≥ 70, while 16 students were declared incomplete with a score ≤ 70 with an average score of 69.1 . These results mean that it is not in accordance with the target set by researchers with learning completeness being 75%. The results of the second cycle test showed that of the 27 class VI students, only 21 students could be declared complete in their studies by getting a score of ≥ 70, while 6 students were declared incomplete with a score of ≤ 70 with an average score of 79.3. These results mean that it is in accordance with the target set by the researchers with learning completeness being 78%.